Valorization of Cappadocia waste earth in the production of sustainable lime-based grouts - Dinc-Sengonul, Burcu; Bayram, Muhammed; Oktay, Didem; Yuzer, Nabi (ELSEVIER, 2024)
Historical structures and natural landscapes in Turkey's Cappadocia Region, a popular tourist spot, have been designated mixed heritage sites on the World Heritage List since 1985. The region's old rock-cut and masonry constructions have been damaged for various reasons. Furthermore, the waste volcanic tuff excavated during the construction of rock-cut structures in the region totals around 10 million tons of waste material per year. It creates severe visual concerns since it cannot be used effectively in the area. Because repairing ancient buildings needs precision, the restoration method and material should be selected based on the structures' structural system and material attributes. Grouting is one of the most common ways of repairing and strengthening masonry buildings or fissured architectural pieces with adequate connected voids. This technique aims to restore damaged structures' continuity, cohesiveness, and strength while keeping their morphology and load-bearing system intact. This research explores the potential use of waste earth from rock-cut structures in the Cappadocia Region in hydraulic limebased grouts. Thus, an injection material that can be used to repair fairy chimneys and historical rock-cut and masonry structures in this region will be produced. Various lime-based grout types containing Cappadocia waste earth (CWE) were produced in this scope. The evaluation of grout performance encompassed assessments in the fresh state (Fluidity, Penetrability, and Volume Stability) and the hardened state (Flexural and Compressive strength). Furthermore, this research delved into how Cappadocia waste earth (CWE) influences the physical and microstructural characteristics of lime-based grouts. Thanks to this study, both environmental pollution will be reduced, and sustainability will be contributed.
Keywords: Waste cappadocia earth; Lime -based grouts; Historic preservation; Sustainability; BLAST-FURNACE SLAG; SILICA FUME; ORTAHISAR CASTLE; STONE MASONRY; MICROSTRUCTURE; INJECTION; STRENGTH; DESIGN; TEMPERATURE; PROTECTION; Chemistry; Science & Technology - Other Topics; Environmental Sciences & Ecology